Reform of Compulsory Licensing of Non-Medicinal Technologies in Indonesian Patent Law - Salsabilah, Nailah; Nashwa Fadila Dewi; Navaratu Annisa Devi; Najwa Alawiyah; Ardila Kurnia, Saskya (VARIA HUKUM, 2025)
This article highlights the need for reforming the regulation of compulsory licensing for non-pharmaceutical technologies in Indonesia by reviewing Law No. 13 of 2016 on Patents. This research employs a normative juridical approach, focusing on normative challenges and the rationale behind the urgency for reform. The findings indicate that current regulation remains limited to the pharmaceutical sector and lacks a clear operational definition of “public interest” in non-pharmaceutical contexts. Moreover, the absence of a Government Regulation outlining technical procedures, as well as the complexity of patent thickets in modern technologies, presents significant challenges. Such reform is essential to broaden access to strategic technologies, promote technology transfer, and reduce the dominance of foreign patents in key sectors of national development.